Wokół symbolu. Kościoły upamiętniające Konstytucję 3 maja - Wroński, Józef Szymon (Acta Universitatis Lodziensis. Folia Historica, 1998)
The 3rd of May Constitution (1791) had an influence not only upon political and social life, but also upon Polish art, including architecture. It can be seen on the example of religious architecture. A zeal for erecting memorial churches appeard shortly after the Constitution was passed. Such buildings were also erected later to memorize the following anniversaries.